The Effectiveness of Communication Practices with the Customers: A Comparative Study between Eastern Bank Limited and Mutual Trust Bank Limited - Rahim, Sheikh Abdur; Tuli, Ferdouse Ara (Asian Business Review, 2013)
Communication has been considered as the lifeblood of every business organization. In case of banking business in Bangladesh, the effective communication is a must for convincing the customers. The reason behind that, the number of banks is increasing day-bay-day. Thus, the competition of banking business in Bangladesh is going to be severely critical for the bankers. So, this paper attempts to explore the tools and techniques used by the bankers of Eastern Bank Limited and Mutual Trust Bank Limited to communicate with their customers. This paper also attempts to reveal the opinion of bankers and customers regarding the effectiveness of communication practices by the authority of Eastern Bank Limited and Mutual Bank Limited and prescribed some possible courses of actions to make the communication more effective with their customers. JEL Classification Code: D83